Impact of whole-grain interventions on serum vitamin D levels in individuals at risk of diabetes - Liu, TingTing; Wang, LiMing; Ou, LingLing; Feng, Jing; Cheng, JiaLi; Gong, ZhaoLong (Frontiers in Nutrition, 2025)
IntroductionWe examined the effects of a whole-grain intervention on serum vitamin D levels in pre-diabetic individuals in China.MethodsParticipants aged 18–65 years at risk of diabetes participated in a 12-week randomised parallel controlled trial. Intervention groups consumed 50 g/day and 100 g/day of whole grains, whereas the control group maintained a regular diet. All participants received nutritional guidance. Serum 25-hydroxyvitamin D levels were monitored at baseline, 6 weeks, and 12 weeks using liquid chromatography–tandem mass spectrometry.ResultsAt 6 weeks, serum 25-hydroxyvitamin D levels remained insufficient across all groups. By 12 weeks, both intervention groups showed significant increases, reaching adequate levels, whereas the control group remained at the lower limit of adequacy.ConclusionSustained whole-grain intake improves vitamin D status in pre-diabetic individuals.